Progress in rice sheath blight resistance research - Chen, Jingsheng; Xuan, Yuanhu; Yi, Jianghui; Xiao, Guosheng; Yuan, De Peng; Li, Dandan (Frontiers in Plant Science, 2023)
Rice sheath blight (ShB) disease poses a major threat to rice yield throughout the world. However, the defense mechanisms against ShB in rice remain largely unknown. ShB resistance is a typical quantitative trait controlled by multiple genes. With the rapid development of molecular methods, many quantitative trait loci (QTLs) related to agronomic traits, biotic and abiotic stresses, and yield have been identified by genome-wide association studies. The interactions between plants and pathogens are controlled by various plant hormone signaling pathways, and the pathways synergistically or antagonistically interact with each other, regulating plant growth and development as well as the defense response. This review summarizes the regulatory effects of hormones including auxin, ethylene, salicylic acid, jasmonic acid, brassinosteroids, gibberellin, abscisic acid, strigolactone, and cytokinin on ShB and the crosstalk between the various hormones. Furthermore, the effects of sugar and nitrogen on rice ShB resistance, as well as information on genes related to ShB resistance in rice and their effects on ShB are also discussed. In summary, this review is a comprehensive description of the QTLs, hormones, nutrition, and other defense-related genes related to ShB in rice. The prospects of targeting the resistance mechanism as a strategy for controlling ShB in rice are also discussed.